The measurement of the size and concentration of fine sand suspensions using scattered ultrasound - Lenn, C. P. (Cranfield University, 1985)
This work is concerned with the development of an instrument capable of measuring simultaneously both the size and concentration . of suspended fine sands in the presence of silt. A review of the literature of the measurement of suspended solids showed that the most promising approach to develop such an instrument would use ultrasonic methods. A theoretical study of the scattering of ultrasound for suspensions is presented and this shows that an appropriate choice of frequency and scattering geometry will give reduced sensitivity to silt size particles whilst yielding information on the size and concentration of the suspended particles. Laboratory experiments were conducted using a vertical sedimentation test facility and single angle scattering from suspensions of sand and glass balls. The experiments showed that the theory is adequately modelled in practice. A laboratory model of a field instrument, employing analogue and digital signal processing, was then constructed and tests were performed on a range of suspended sediments with different mean size, The ratio of ultrasound scattered through 10° and 170° was found to be concentration independent, being a function of size only. The ultrasound scattered through 10°. suitably processed, was a measure of concentration. A measure of agreement between theoretical predictions and experimental results was obtained and design recommendations for the manufacture of a field instrument are given.